Distribution of Arsenic, Copper, Lead, Zinc elements in water and soils of sulfur deposits in the North West of Hanoi - Mai, Dang; Vuong, Nguyen Van; Ngu, Nguyen Trong (VNU Journal of Science: Earth and Environmental Sciences; Vol 25 No 2, 2009)
Abstract